Effectiveness of Various Natural β-Carotene Sources in Feed on the Color Brightness of Goldfish (Carassius auratus) - Tubagus Luthfianda; Bambang Hendra Siswoyo; Dwi Tika Afriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to analyze the effect of incorporating several natural sources of β-carotene into feed on improving the color brightness of goldfish. An experimental method was employed using a completely randomized design (CRD) with four treatments and three replications: P1 as the control, P2 with carrot powder, P3 with papaya powder, and P4 with tomato powder, each added to the feed at the same dosage. Color brightness was measured using a color-chart-based scale analysis, and the resulting data were analyzed using one-way ANOVA followed by Tukey’s post hoc test. The results showed no significant differences among treatments during the initial observation period (F = 1.916; p = 0.129). However, significant differences were observed in the subsequent assessment (F = 461.230; p < 0.001; η² = 0.894). The highest color brightness was recorded in P2, which received carrot powder, followed by P3 with papaya powder, P4 with tomato powder, and P1 as the control. These findings indicate that natural sources of β-carotene have a strong effect on enhancing the color brightness of goldfish. They also provide practical implications for developing natural feeds based on locally available ingredients for ornamental fish culture.